Role of Compatibilizer on Morphological and Mechanical Properties of Low Cost Polypropylene/Wood Flour Composites - Bhandari, Netra L.; Thomas, Sabu; Das, Chapal K.; Adhikari, Rameshwar (Journal of Nepal Chemical Society, 2013)
Wood flour (WF) reinforced polypropylene (PP) composites were studied with special attention to morphology and mechanical properties of the composites and the effectiveness of chemically modified fillers to improve their mechanical properties. The composites of polypropylene with neat wood flour and treated wood flour of Sorea robusta in different proportions were prepared by melt mixing followed by compression molding. Maleic anhydride grafted polypropylene (MA-g-PP) was used as compatibilizer. The samples were characterized by Fourier Transform Infrared (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), tensile testing, and water absorption testing. The results show that the alkali treated WF is more compatible with PP matrix than the neat one and the effects are reflected in the morphological and mechanical properties of the composites. The compatibilizer has been found to play key role to enhance the filler-matrix interfacial interactions. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9276 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 113-120 Uploaded date: 12/6/2013